3D-PRINTED AND PERSONALIZED ORTHOPEDIC IMPLANTS: FUNCTIONAL OUTCOMES AND RETURN TO SPORT – A STRUCTURED REVIEW - Podeszwa, Sebastian; Rolski, Wiktor; Przybylska, Zuzanna; Michalska, Paulina; Przystaś, Bartłomiej; Grzechowiak, Magdalena; Purpura, Aleksandra Anna; Hobot, Mikołaj Piotr; Dobosz, Gabriela Patrycja (International Journal of Innovative Technologies in Social Science, 2026)
Background: Conventional orthopedic implants are standardized and may not fully reflect individual anatomical variability and biomechanics, particularly in physically active patients. Advances in additive manufacturing (3D printing) and personalized alignment strategies have enabled the development of patient-specific solutions aimed at improving functional outcomes. Aim: To evaluate the effectiveness of 3D-printed and personalized orthopedic implants in improving functional outcomes and facilitating return to sport. Methods: A structured review of 31 studies identified through PubMed, Scopus, and Google Scholar was conducted. The analysis included knee and hip procedures utilizing additive manufacturing, patient-specific instrumentation, and alignment strategies such as kinematic alignment (KA) and restricted kinematic alignment (rKA). Outcomes included patient-reported measures (KOOS, Forgotten Joint Score, WOMAC), implant survivorship, complication rates, and return-to-sport (RTS). Results: Personalized approaches demonstrated comparable or superior functional outcomes compared to conventional techniques. Improvements in KOOS Sport and Forgotten Joint Scores were reported in knee procedures. In total knee arthroplasty, rKA showed high survivorship (up to 98%) and favorable functional outcomes. RTS rates ranged from 70% to 100%, with a shift toward low-impact activities. In hip arthroplasty, personalized planning and advanced materials improved implant performance without increasing complication rates. Overall, complication rates remained low and comparable to standard approaches. Conclusions: 3D-printed and personalized implants represent a safe and effective advancement in orthopedic care, improving function and supporting return to physical activity. Further high-quality, long-term studies are needed to confirm durability, cost-effectiveness, and broader applicability.